LYVE-1 is not restricted to the lymph vessels - Nasser, Selim M. (2001)
Lymphatic vessel endothelial hyaluronan receptor (LYVE)-1 is thought to be restricted to lymph vessels and has been used as such to show that tumor lymphangiogenesis occurs on overexpression of lymphangiogenic factors in mouse tumor models. However, these studies have not yet been corroborated in human tumors. Here we show, first, that LYVE-1 is not exclusive to the lymph vessels. Indeed, LYVE-1 is also present in normal hepatic blood sinusoidal endothelial cells in mice and humans. Surprisingly, LYVE-1 is absent from the angiogenic blood vessels of human liver tumors and only weakly present in the microcirculation of regenerative hepatic nodules in cirrhosis, though both vessels are largely derived from the liver sinusoids. Second, we propose a novel approach to identify lymphatics in human and murine liver. By combining LYVE-1 and Prox 1 (a transcription factor) immunohistochemistry, we demonstrate that lymphatics are abundant in cirrhosis. In contrast, in human hepatocellular carcinoma and liver metastases, they are restricted to the tumor margin and surrounding liver. The absence of intratumor lymphatics in hepatocellular carcinomas and liver metastases may impair molecular and cellular transport in these tumors. Finally, the presence of LYVE-1 in liver sinusoidal endothelia suggests that LYVE-1 has functions beyond the lymph vascular system.